Relationships Between Vitamin D Status and Cytokine: Results from Interferon-Based Therapy in Non-Cirrhotic, Treatment-Naïve Patients with Chronic Hepatitis C Infection - Chen HW (Dove Medical Press, 2020)
Hsuan-Wei Chen,1 Yi-Lin Chiu,2 Tsai-Yuan Hsieh,1 Peng-Jen Chen,1 Tien-Yu Huang,1 Hsuan-Hwai Lin,1 Yu-Lueng Shih,1 Jung-Chun Lin1 1Division of Gastroenterology, Department of Internal Medicine, Tri-Service General Hospital, National Defense Medical Center, Taipei, Taiwan; 2Department of Biochemistry, National Defense Medical Center, Taipei, TaiwanCorrespondence: Jung-Chun LinDivision of Gastroenterology, Department of Internal Medicine, Tri-Service General Hospital, National Defense Medical Center, 325, Sec 2, Cheng-Kung Road, Neihu 114, Taipei, TaiwanTel +886-2- 87927409Fax +886-2- 87927139Email doc10506@gmail.comBackground: Vitamin D contributes to bone health and extra-skeletal effects. The mechanisms underlying vitamin D metabolism have not been extensively evaluated. The relationships between vitamin D and inflammatory cytokines are debated. Our objective was to investigate whether supplemental interferons are associated with longitudinal change of vitamin D status in humans.Methods: A total of 48 patients with 24 or 48 weeks of pegylated interferon-α plus ribavirin therapy were examined for serum 25-hydroxyvitamin D (25[OH]D) level before treatment, at the end of treatment, and 24 weeks after treatment. In addition, we analyzed publicly available RNA sequencing data from accession GSE42697 and GSE7123 in the Gene Expression Omnibus.Findings: The overall sustained virologic response (SVR) rate was 62.5%. There was no statistically significant association between baseline 25(OH)D concentrations and liver fibrosis. In patients with SVR, serum 25(OH)D increased markedly at end-of-treatment and decreased markedly by the end of the 24-week follow-up period. In the non-SVR group, this treatment-dependent change was lost. In gene expression analysis, the vitamin D biosynthesis process was activated in subjects with SVR, but not in patients without SVR. Furthermore, vitamin D receptor (VDR) signaling in peripheral blood mononuclear cells (PBMCs) was triggered in marked responders but not in poor responders.Conclusion: In the aggregate, these data suggest that interferons have a regulatory influence on vitamin D status that can contribute to VDR signaling in PBMCs.Keywords: cytokines, interferon-α, PBMCs, VDR signaling, vitamin D